Digital Based Early Detection of Mental Health in Mental Health Alert Village - Zaini, Mad; Komarudin, Komarudin; Abdurrahman, Ginanjar (GLOBAL HEALTH SCIENCE GROUP, 2023)
Mental health is an integral part of being healthy. Some mental health indicators are also indicators of a healthy state such as being free from pain or psychological distress, being productive and contributing to social life. This study aims to describe community mental health based on the results of early detection using the e-DSSJ application. The research design used is descriptive with a case study approach. The subjects used in this study were the people of Botolinggo village, Bondowoso district. The research sample of 1040 respondents was taken by purposive sampling with inclusion criteria, namely aged ≥ 15 years, domiciled in Botolinggo Village and willing to become research respondents. The instrument used in this study is the e-DSSJ application which adopts the Self Reporting Questionaire-29 (SRQ-29) instrument. The results of univariate analysis showed that most respondents were mentally healthy (73%), experienced anxiety (26.7%), mental disorders (0.09%) and no respondents experienced post-traumatic distress syndrome (PTSD) and drug abuse (0%). Through early detection of mental health based on the e-DSSJ application, it can be seen that people who are mentally healthy, at risk of mental problems and mental disorders with the hope that those who are mentally healthy remain healthy, those at risk of mental problems do not experience mental disorders and those with mental disorders can immediately get health services.